THE DYNAMIC APPROACH FOR MALAYSIAN PADDY FARMERS: FACTORS AFFECTING THE ADOPTION TO PRIORITIZE GREEN FERTILIZER - ADNAN, NADIA (2020)
One of the innovations introduced towards tackling the heightening concern of environmental impact is Green technology